2019
DOI: 10.1177/1759720x19844632
|View full text |Cite
|
Sign up to set email alerts
|

The role of microbiome in rheumatoid arthritis treatment

Abstract: Rheumatoid arthritis (RA) is an autoimmune disorder with multifactorial etiology; both genetic and environmental factors are known to be involved in pathogenesis. Treatment with disease-modifying antirheumatic drugs (DMARDs) plays an essential role in controlling disease progression and symptoms. DMARDs have immunomodulatory properties and suppress immune response by interfering in various pro-inflammatory pathways. Recent evidence has shown that the gut microbiota directly and indirectly modulates the host im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(84 citation statements)
references
References 133 publications
3
80
0
1
Order By: Relevance
“…Earlier reports have demonstrated association of lower bacterial diversity with the disease condition (34,35). In our study, a significantly lower number of observed OTUs was found in NewDMs compared to ND, which increased in KnownDMs on antidiabetic treatment (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…Earlier reports have demonstrated association of lower bacterial diversity with the disease condition (34,35). In our study, a significantly lower number of observed OTUs was found in NewDMs compared to ND, which increased in KnownDMs on antidiabetic treatment (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…Numerous studies have explored the therapeutic effects of HUMSCs that mediate the balance between Tregs and Th17 cells in RA (Ma et al, 2019). Several researchers have explored the effect and mechanism of other drugs on RA from the perspective of the gut microbiota (Bodkhe et al, 2019). However, no researchers have linked Tregs/Th17 cells with the gut microbiota to elucidate the therapeutic mechanism of HUMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…2) In the germ-free model, parenteral injection of cell wall fragments of exogenous intestinal bacteria can induce arthritis (Scher et al, 2013;Bernard, 2014). 3) Partial gut microbiome of clinical RA patients restored to normality after antirheumatic treatment (Zhang et al, 2015;Bodkhe et al, 2019). 4) Existing reports have shown that diet could affect the activity of inflammation, and high-fat diet has a negative effect on intestinal permeability (Skoldstam et al, 2003;Rohr et al, 2020).…”
Section: Gut Microbiome In the Etiology Of Rheumatoid Arthritismentioning
confidence: 99%